Effects of vitamin D supplementation on muscle strength in athletes: A systematic review - Chiang, C. -M.; Ismaeel, A.; Griffis, R. B.; Weems, S. (The Journal of Strength and Conditioning Research, 2017)
The purpose of this systematic review of the literature was to investigate the effects of vitamin D supplementation on muscle strength in athletes. A computerized literature search of 3 databases (PubMed, MEDLINE, and Scopus) was performed. Included in the review were randomized controlled trials (RCTs), published in English, which measured serum vitamin D concentrations and muscle strength in healthy, athletic participants aged 18-45 years. Quality was assessed using the PEDro scale. Five RCTs and 1 controlled trial were identified, and quality assessment showed 5 trials were of "excellent quality" and 1 was of "good quality." Trials lasted from 4 weeks to 6 months and dosages ranged from 600 to 5,000 International Units (IU) per day. Vitamin D2 was found to be ineffective at impacting muscle strength in both studies wherein it was administered. In contrast, vitamin D3 was shown to have a positive impact on muscle strength. In 2 studies, strength outcome measures were significantly improved after supplementation (p = 0.05). In the other 2 studies administering vitamin D3, there were trends for improved muscle strength. Specifically, improvements in strength ranged from 1.37 to 18.75%. Additional studies are needed to confirm these associations.